2017
DOI: 10.1002/hpm.2481
|View full text |Cite
|
Sign up to set email alerts
|

Planning without action and action without planning? Examining a regional health system's efforts to improve patient flow, 1998–2013

Abstract: Most health care organizations engage in formal and informal planning, yet their improvement initiatives may remain disjointed and reactive. Research on organizational decision-making has found that the "discovery" approach (seek and assess multiple options before selecting one) outperforms "idea imposition" (identify 1 option, then gather information to [dis]confirm it), yet is observed relatively infrequently. Might this imply that discovery frequently collapses before fruition? This qualitative study sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Calgary Zone participants reported that this approach initially yielded significant improvements in ED flow, but effects deteriorated after two to three years because such pressure could not be maintained indefinitely (Kreindler et al 2020). The most common regional strategy has centred on encouraging local players to develop their own initiatives, whether through Lean or ad hoc methods (Kinsman et al 2014;Kreindler 2018). As noted, such an approach succeeded in the two geographies of AHS South Zone, but other regions' attempts (which have, of course, varied widely in content and context) have not shown similar results.…”
Section: Capacity Increasesmentioning
confidence: 99%
“…Calgary Zone participants reported that this approach initially yielded significant improvements in ED flow, but effects deteriorated after two to three years because such pressure could not be maintained indefinitely (Kreindler et al 2020). The most common regional strategy has centred on encouraging local players to develop their own initiatives, whether through Lean or ad hoc methods (Kinsman et al 2014;Kreindler 2018). As noted, such an approach succeeded in the two geographies of AHS South Zone, but other regions' attempts (which have, of course, varied widely in content and context) have not shown similar results.…”
Section: Capacity Increasesmentioning
confidence: 99%
“…Study 2 chronicled a Canadian regional health system's strenuous, unsuccessful efforts to reduce emergency department wait times and improve patient flow. (Research methods, which included review of approximately 700 documents; in‐depth interviews with 62 senior, middle, and departmental managers; and quantitative analysis of flow indicators, have been described elsewhere …”
Section: Explaining Success and Failure: The Spiral And The Stalematementioning
confidence: 99%
“…(Research methods, which included review of approximately 700 documents; in-depth interviews with 62 senior, middle, and departmental managers; and quantitative analysis of flow indicators, have been described elsewhere. 53 ) Initially, leaders sought to gain greater control over system outcomes (need for precision) by promoting pan-regional consistency, which curtailed hospitals' freedom to innovate (weakening stim). (It should be noted that the region's strategy did not include high-precision stip strategies, such as redesign of services based on rigorous analysis of the flow problem, or introduction of powerful mechanisms to hold hospitals accountable for performance.)…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…5 Tight decision-making timelines are sometimes characterized as a good reason why decision-makers cannot wait for research findings, although this characterization seems open to question: In one documented case, a health system made repeated, unsuccessful efforts, spanning more than a decade, to solve one particular problem; each effort was marked by a flurry of panicked activity and an insistence that there was no time for further information-gathering or deliberation. 6 On this note, there are many bad reasons – some mentioned in this article, others elsewhere. For example, decision-makers may request evidence on a decision so highly politicized, or under the control of individuals with such rigid opinions, that the “voice” of research is sure to be silenced.…”
mentioning
confidence: 91%